Knowledge, attitude and perceptions towards antimicrobial use in small animals among veterinary practitioners and students at a university veterinary teaching hospital in Malaysia - Chee, F. M. F.; Chen, H.C. (Malaysian Veterinary Medical Association, 2023)
Companion animals have been suggested as potential reservoirs of antimicrobial resistance. In Malaysia, qualitative study on the use of antimicrobials in small animals is limited. This study aimed to determine the knowledge, attitude, and perceptions towards antimicrobial use in small animals among veterinary practitioners and students at University Veterinary Teaching Hospital (UVH), Universiti Putra Malaysia. An online self-administered questionnaire was developed. All fourth and final year students, and practitioners from UVH small animal practice were invited to participate voluntarily. A total of 140, out of 238 invitees (59%) responded. Overall, the respondents showed desirable perceptions and attitude towards the issue of antimicrobial resistance and prudent use of antimicrobials. Only 66.4% of respondents were confident of their knowledge. Culture and sensitivity test, client compliance and clinical signs were the top most important factors being considered for antimicrobial prescription. Scientific literature was the most chosen source of information while antimicrobial stewardship guidelines appeared to be the least popular. Amoxicillin-clavulanate was the most chosen antibiotic for all the clinical scenarios of dog spay, feline upper respiratory tract disease (FURD), feline lower urinary tract disease (FLUTD) and surface pyoderma. Second commonly chosen antibiotic was the fluoroquinolones, mainly by veterinary students for FURD, FLUTD and pyoderma. Results suggest the needs for more training on the latest international or national guidelines on antibiotic choices according to the clinical conditions or body systems.